Cadence-power-relationship during decisive mountain ascents at the Tour de France - Vogt, S.; Roecker, K.; Schumacher, Y. O.; Pottgiesser, T.; Dickhuth, H. H.; Schmid, A.; Heinrich, L. (International Journal of Sports Medicine, 2008)
The aim of the study was to report the relationship between cadence and power developed by professional cyclists during high mountain ascents of the Tour de France. From the 10 cyclists (30 ± 4 years, 178 ± 8 cm, 69 ± 6 kg) involved in the study, 108 ascents were recorded and analyzed using a mobile power measurement device (SRM Training Systems, Jülich, Germany). Based on topographic characteristics, the ascents were categorized into 1st and Hors Category (HC) climbs. During the ascents of the 1st Category climbs, power output averaged 312 ± 43 W (4.5 ± 0.6 W/kg) with a mean cadence of 73 ± 6 rpm and a mean duration of 37 : 41 ± 16 : 16 min. Power output averaged 294 ± 36 W (4.3 ± 0.6 W/kg) at a mean cadence of 70 ± 6 rpm during 57 : 40 ± 10 : 32 min on HC climbs. The maximal mean power for long durations (1800 s) showed a mean power output of 327 W and 346 W for the 1st and HC climbs, respectively. The evaluation of the cadence-power output and the distance per pedaling cycle-power output relationship shows that high power outputs are mainly yielded by higher pedaling cadences and higher gears.